Multicolor Immunofluorescent Imaging of Complex Cellular Mixtures on Micropallet Arrays Enables the Identification of Single Cells of Defined Phenotype. Issue 7 (29th February 2016) - Westerhof, Trisha M.; Li, Guann‐Pyng; Bachman, Mark; Nelson, Edward L.
Abstract : A Micropallet‐Array‐based strategy allowing the identification of cells of defined phenotype in complex mixtures, such as would be obtained from a tissue biopsy, is presented. Following the distribution of single adherent cells from the mixture on individual pedestals, termed "micropallets", immunofluorescent confocal imaging is applied to interrogate the expression of five cell surface molecules.